CONSTRUCTION AND EXPRESSION OF QUARTET RECOMBINANT PEPTIDE SURFACTANT FOR EOR APPLICATION - Cut Nanda Sari; Usman Usman; Refiana Lestary; Riesa Khairunnisa W.R.; Leni Herlina; Syafrizal Syafrizal; Tati Kristianti; Sony Suhandono (Scientific Contributions Oil and Gas, 2016)
The main drawback of the SUPEL peptide surfactant product which has been developed for EOR application is it isunstable at a high temperature. This research is aimed at generating the prototype of peptide surfactant construction in recombinant by stringing up 4 SUPEL linier sequences. Quartet recombinant technology can produce the peptide surfactant characterized as reversible biosurfactant, which is active at high temperature but inactive at low temperature. Multiple SUPEL Construction (MSC) that was developed in this research is using synthetic DNA and producing SUPEL in 4 sequences that can flip at normal temperature and can open when heated. SDS PAGE analysis results show that MSC construction can be expressed by inducting IPTG and cell harvested at 90°C. This research proves that construction and expression of the SUPEL quartet has been achieved by producing the peptide at an ideal size.